2022
DOI: 10.3390/antibiotics11060810
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Antibiotic Use among Hospitalized Patients according to WHO Access, Watch, Reserve (AWaRe) Classification: Findings from a Point Prevalence Survey in Bangladesh

Abstract: For supporting antibiotic stewardship interventions, the World Health Organization (WHO) classified antibiotics through the AWaRe (Access, Watch, and Reserve) classification. Inappropriate use of antimicrobials among hospital-admitted patients exposes them to the vulnerability of developing resistant organisms which are difficult to treat. We aimed to describe the proportion of antibiotic use based on the WHO AWaRe classification in tertiary and secondary level hospitals in Bangladesh. A point prevalence surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
(46 reference statements)
3
11
1
Order By: Relevance
“…However, the use of the Watch class antibiotics was relatively lower than reported in a study conducted in Bangladesh where 64% of the prescribed antibiotics were in the Watch class. Similar to a previous study (Rashid et al, 2022), medical wards had the highest use of antibiotics in the Watch class.…”
Section: Discussionsupporting
confidence: 82%
“…However, the use of the Watch class antibiotics was relatively lower than reported in a study conducted in Bangladesh where 64% of the prescribed antibiotics were in the Watch class. Similar to a previous study (Rashid et al, 2022), medical wards had the highest use of antibiotics in the Watch class.…”
Section: Discussionsupporting
confidence: 82%
“…However, PPSs conducted in neighbouring countries found prescribing rates of 100% in Bangladesh and 97.3% and 89.67% in Pakistan, far higher than at other times [ [23] , [24] , [25] ]. Our PPS, conducted immediately after a COVID-19 wave, found an antibiotic prescription rate of 41.73 %, which was much lower than the antibiotic prescription rates reported in regional PPSs conducted during a COVID-19 wave and was comparable to the antibiotic prescription rates reported in regional PPSs conducted prior to a COVID-19 wave [ 9 , 10 , [19] , [20] , [21] , [22] , [22] , [22] , [23] , [24] , [25] ]. In contrast to the developing nations of the Indian subcontinent, most developed nations of Europe and America had substantial lower antimicrobial prescription rates (25-34%) in the pre-COVID-19 period [ [26] , [27] , [28] ].…”
Section: Discussioncontrasting
confidence: 44%
“…Another pre-COVID-19 wave PPS in a major tertiary care Indian hospital reported an antibiotic prescription rate of 50.9 % [ 19 ]. Even higher rates of antibiotic prescription were reported in pre-COVID-19 studies from neighbouring countries: 78% in Bangladesh, 77.16% in Pakistan, and 63.4% in Myanmar [ [20] , [21] , [22] ]. Data on antibiotic prescribing in India during major COVID-19 waves are sparse [ 18 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our results showed that during the study, the most commonly used antibiotics were third-generation cephalosporins, especially ceftriaxone. Results from the study of AU in tertiary hospitals in Bangladesh showed that cephalosporins constituted around 50% of all antibiotics used, especially third-generation cephalosporins, with extensive use of ceftriaxone [ 21 ]. Use of this class of antibiotics is lower than 50% in our hospital.…”
Section: Discussionmentioning
confidence: 99%